The Transcriptome of Latent Human Cytomegalovirus - Schwartz, Michal (J Virol, 2019)
The latent human cytomegalovirus (HCMV) transcriptome has been extremely difficult to define due to the scarcity of naturally latent cells and the complexity of available models. The genomic era offers many approaches to transcriptome profiling that hold great potential for elucidating this challenging issue. The results from two recent studies applying different transcriptomic methodologies and analyses of both experimental and natural samples challenge the dogma of a restricted latency-associated transcription program. Instead, they portray the hallmark of HCMV latent infection as low-level expression of a broad spectrum of canonical viral lytic genes.